Early Aptian black-shales in the Boreal Realm: calcareous nannofossil and stable isotope evidence for regional and global processes - C. Bottini; E. Erba; J. Mutterlose (2011)
The early Aptian is marked by a global phenomenon of widespread deposition of organic carbon-rich sediments under oxygen-poor conditions known as Oceanic Anoxic Event 1a (OAE 1a: ~120 Ma). Triggering mechanisms for the OAE 1a are thought to have been the emplacement of the Ontong Java Plateau, associated with global warming and enhanced primary productivity. In northern Germany the OAE 1a has its sedimentary expression in the “Fischschiefer” characterized by finely laminated black shales rich in organic matter. In the Early Cretaceous northern Germany was part of the Lower Saxony Basin being a marginal epicontinental sea forming the southern extension of the Boreal-Arctic Sea, thus located between the Boreal Realm in the north and the Tethys in the south. The relatively restricted palaeogeographic settings probably exerted a regional control on the deposition of the Fischschiefer. We investigated the Upper Barremian-Lower Aptian interval in three sites from northern Germany (Alstätte, Rethmar, Hoheneggelsen KB 9) applying a multidisciplinary approach, bringing together the biotic and ocean chemistry responses across OAE 1a. Specifically, we performed calcareous nannofossil (abundance and assemblage composition) and carbon and oxygen stable-isotope analyses. Calcareous nannoplankton is sensitive to changes in temperature, fertility and chemistry of surface-waters, therefore it is the ideal tracer for reconstructing palaeoclimatic and palaeoceanographic fluctuations. The direct calibration of the nannofossil and geochemical data is fundamental to provide a coherent reconstruction of the perturbations across OAE 1a. The main objective of this study is to reconstruct palaeoclimatic, palaeoecological and palaeoceanographic factors that controlled the deposition of the Fischschiefer in the Lower Saxony Basin. The results obtained for the Boreal Realm are compared and integrated with biotic and geochemical proxies collected across the OAE 1a from the Tethys (Cismon, N. Italy), with the main purpose of understating the ...